Mechanistic insights into stereoselective catalysis-the effects of counterions in a CuII-bissulfoximine-catalyzed Diels-Alder reaction. - Bolm, C; Martin, M; Gescheidt, G; Palivan, C; Stanoeva, T; Bertagnolli, H; Feth, M; Schweiger, A; Mitrikas, G; Harmer, J (2007)
The initial steps of an enantioselective Diels-Alder reaction catalyzed by a CuII-bissulfoximine complex were followed by EXAFS (EXAFS=extended X-ray absorption fine structure), EPR (EPR=electron paramagnetic resonance) spectroscopy (CW-EPR, FID-detected EPR, pulse ENDOR, HYSCORE; CW=continuous wave; ENDOR=electron nuclear double resonance; HYSCORE=hyperfine sublevel correlation; FID=free induction decay), and UV-visible spectroscopy. The complexes formed between the parent CuX2 (X=Cl-, Br-, TfO-, SbF6-) salts, the chiral bissulfoximine ligand (S,S)-1, and N-(1-oxoprop-2-en-1-yl)oxazolidin-2-one (2) as the substrate in CH2Cl2 were investigated in frozen and fluid solution. In all cases, penta- or hexacoordinated CuII centers were established. The complexes with counterions indicating high stereoselectivity (TfO- and SbF6-) reveal one unique species in which substrate 2 binds to pseudoequatorial positions (via O atoms), shifting the counterions to axial locations. On the other hand, those lacking stereoselectivity (X=Cl- and Br-) form two species in which the parent halogen anions remain at equatorial positions preventing the formation of geometries compatible with those found for X=TfO- and SbF6-.